2005
DOI: 10.5172/conu.20.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Women’s views of registered nurses as Papanicolaou smearproviders: A pilot study

Abstract: While women are positive about RN PSPs, there is a need for promotion and community education about the role of RNs in providing cervical screening services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In an investigation of women’s views of registered nurses as ‘Pap smear’ providers Christie et al [1] found high levels of acceptance of “a female health professional [providing] a Pap smear” [1] (p.166) which agrees with findings from this study. These authors go on to argue that clients are less likely to accept cervical screening conducted by male PNs, citing personal comfort and the sensitivity of female clinicians as influencing factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In an investigation of women’s views of registered nurses as ‘Pap smear’ providers Christie et al [1] found high levels of acceptance of “a female health professional [providing] a Pap smear” [1] (p.166) which agrees with findings from this study. These authors go on to argue that clients are less likely to accept cervical screening conducted by male PNs, citing personal comfort and the sensitivity of female clinicians as influencing factors.…”
Section: Discussionsupporting
confidence: 87%
“…While previous studies have examined the role of PNs as Pap smear [cervical screening] providers [1-4] findings are limited to identifying barriers to implementing the role, while recommending further research in the area. This study builds on previous work in order to develop a solutions based approach for PNs and their employing general practices wishing to incorporate cervical screening and well women’s health care services into their work.…”
Section: Introductionmentioning
confidence: 99%
“…Even though general practice is positioned alongside other primary care service models, such as family planning services, where nurses are successfully employed to provide well women health checks as a part of their role (Christie et al 2005), barriers were identified for participants who wished to expand their role which can be attributed to context and culture. In particular, the genderization of medicine and the role of the female general practitioner was found to impact greatly on the ability of practice nurses to change their role to incorporate cervical screening, traditionally seen as a the business of female doctors.…”
Section: Discussionmentioning
confidence: 99%
“…They found that members of the public were uncomfortable with PNs undertaking advanced roles, including cervical screening. A more recent study, however, reported positive attitudes to registered nurse ‘Pap‐smear’ providers. Although public confidence might be expected to have increased as service users have become more familiar with the role of the PN, the rate at which PNs actually undertake cervical screening suggests otherwise.…”
Section: Australian Practice Nurses and Cervical Screeningmentioning
confidence: 92%